TEORI STRING DAN TEORI-M - Muhamad, Roby
Abstract : We studied five distinct consistent superstring theories. They are, type I, type IIA, type IIB, heterotic SO(32), and heterotic E8 x E8 superstring theory. Analyzingthe pelt ubative duality, the T-duality, we found relationship between type HA and type IIB superstring theory, and between the two heterotic theories. We showed the existence of solitonic solution as a hyperplane called D-brane.Utilizing S-duality, the strong-weak coupling duality, we related the type I theory to the SO(32) heterotic theory. We also showed that the type IIB theory is selfdual. Using the notion of orbifold, we found duality between type I and type HA theory. Finally, by looking at the strong coupling limit region of type HA and E8 x E8, we argue the existence of an hypothetical theory , M-theory, which live in eleven dimensions.